Evaluation of Sanitation Risk Index to Achieve Sustainable Development Goals 2020 in Sanitation Sector - Arimbawa, I. Gede (International Journal of Integrated Engineering, 2020)
Challenges concerning fresh and clean water for drink coupled with sanitation in Indonesia becomes larger than before. It is not only happened in the East area but also all over Indonesia. Continuing the successful of Millennium Development Goals program in 2000 – 2015, government of the developing countries are planning to establish Millennium Sustainable Development Goals program for the period of 2015 - 2030. Evaluation and Assessment of Environmental Health Risk is a research which dedicate to achieve the aims of Sustainable Development Goals (SDGs) in 2020. The present study shows sanitation access of villages in Surabaya concerning drinking water, domestic wastewater, solid waste and drainage as follow: achieves 96,75 % target of drinking water, achieves 94,14% target of domestic wastewater, achieves 96,75% target of solid wastewater, and achieves 92,86% target of drainage. Average Surabaya city achievements in the sanitation sector were 95.125%, it shows villages in Surabaya already achieve the aims of the Sustainable Development Goals program mainly in sanitation sector.